2014
DOI: 10.1080/15567036.2011.574189
|View full text |Cite
|
Sign up to set email alerts
|

Pyrolysis of Sugar Beet Bagasse for Production of Liquid Fuels

Abstract: Sugar beet bagasse was pyrolyzed in a fixed-bed reactor. The temperature of pyrolysis, heating rate, and sweep gas flow rate were varied in the ranges of 350-550 ı C, 10-30 ı C min 1 , and 100-200 cm 3 min 1 , respectively. The maximum oil yield of 26.71% was obtained at a pyrolysis temperature of 500 ı C, heating rate of 30 ı C min 1 , and sweeping gas flow rate of 100 cm 3 min 1 . The elemental analyses and calorific values of the bio-oil were determined, and then the chemical compositions of the bio-oil wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 31 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…However, alternative uses of such valuable byproducts of the sugar industry are currently being investigated to enhance its valorization. These mostly include the use of SBP as a carbohydrate source for the production of (i) food fibers to be incorporated into bread, cookies, spaghetti, and meat products and (ii) biofuels, especially liquid fuels such as bio-oil and bioethanol . Chen et al also investigated the use of SBP as a filler in poly­(lactic acid) composites, whereas Pavier and Gandini evaluated the possible use of SBP as a source of polyol for the production of urethanes and polyurethanes.…”
Section: Introductionmentioning
confidence: 99%
“…However, alternative uses of such valuable byproducts of the sugar industry are currently being investigated to enhance its valorization. These mostly include the use of SBP as a carbohydrate source for the production of (i) food fibers to be incorporated into bread, cookies, spaghetti, and meat products and (ii) biofuels, especially liquid fuels such as bio-oil and bioethanol . Chen et al also investigated the use of SBP as a filler in poly­(lactic acid) composites, whereas Pavier and Gandini evaluated the possible use of SBP as a source of polyol for the production of urethanes and polyurethanes.…”
Section: Introductionmentioning
confidence: 99%
“…Initially gas yield decreased but as the temperature increased gas yield also increased. It can be concluded that at higher than optimum temperatures, the bio‐oil yield decreases due to gasification reactions and secondary cracking reactions, and favours the gaseous products ,. The similar trends were observed for maize stalk by Z. Ji‐lu, Jatropha curcas de‐oiled seed cake by C.H.…”
Section: Resultsmentioning
confidence: 99%
“…The production of bio-liquid and other products by pyrolysis of biomass species has been extensively studied during the past years (Demiral, 2014;Demirbas et al, 2013;Ertas and Alma, 2010;Ö zbay and Pu¨tu¨n, 2014). The aim of this study was to determine the yields of bio-liquid, bio-char, and gaseous products obtained from pyrolysis of cherry laurel (Prunus Laurocerasus L.) seed in the presence of Na 2 CO 3 .…”
Section: Introductionmentioning
confidence: 99%